2018
DOI: 10.1038/s41380-018-0283-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the KCNQ channel opener ezogabine on functional connectivity of the ventral striatum and clinical symptoms in patients with major depressive disorder

Abstract: Major depressive disorder (MDD) is a leading cause of disability worldwide, yet current treatment strategies remain limited in their mechanistic diversity. Recent evidence has highlighted a promising novel pharmaceutical target—the KCNQ-type potassium channel—for the treatment of depressive disorders, which may exert a therapeutic effect via functional changes within the brain reward system, including the ventral striatum. The current study assessed the effects of the KCNQ channel opener ezogabine (also known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…In a recent clinical study, the KCNQ-selective channel potentiator ezogabine was shown to have an antidepressant effect in subjects with MDD [62]. Interestingly, ezogabine administration is associated with an improvement in depressive and anhedonic symptoms together with decreased functional connectivity between the ventral caudate, midcingulate cortex, and posterior cingulate cortex [62]. These results suggest that the antidepressant action of ezogabine may in part be mediated by NAc circuitry, presumably by decreasing excessive activity within this structure.…”
Section: Potentiated Vh → Nacmsh D1-msn Activity Defines Stress-inducmentioning
confidence: 96%
See 1 more Smart Citation
“…In a recent clinical study, the KCNQ-selective channel potentiator ezogabine was shown to have an antidepressant effect in subjects with MDD [62]. Interestingly, ezogabine administration is associated with an improvement in depressive and anhedonic symptoms together with decreased functional connectivity between the ventral caudate, midcingulate cortex, and posterior cingulate cortex [62]. These results suggest that the antidepressant action of ezogabine may in part be mediated by NAc circuitry, presumably by decreasing excessive activity within this structure.…”
Section: Potentiated Vh → Nacmsh D1-msn Activity Defines Stress-inducmentioning
confidence: 96%
“…The importance of K + channels as therapeutic targets in the context of mood disorders is rapidly emerging [60,61]. In a recent clinical study, the KCNQ-selective channel potentiator ezogabine was shown to have an antidepressant effect in subjects with MDD [62]. Interestingly, ezogabine administration is associated with an improvement in depressive and anhedonic symptoms together with decreased functional connectivity between the ventral caudate, midcingulate cortex, and posterior cingulate cortex [62].…”
Section: Potentiated Vh → Nacmsh D1-msn Activity Defines Stress-inducmentioning
confidence: 99%
“…One important mechanism of action for lithium is the blockade of GSK3β, which has many downstream targets including KCNQ2/3 [48]. Early pharmacological evidence suggests a potential mechanistic role of KCNQ3 regulators in mood disorders [36]. Our findings suggest that KCNQ3 effects should also be investigated in suicidal patients.…”
Section: Discussionmentioning
confidence: 72%
“…Ezogabine is an antiepileptic drug that acts primarily by opening neuronal voltage-gated potassium channels of the KCNQ (Kv7.2-7.5) family and it might also exert its therapeutic effects through the augmentation of currents mediated by GABA [34,35]. Recently, KCNQ-type potassium channels have been highlighted as a promising target for future drug discovery efforts in mood disorders, after an open-label study with ezogabine in patients with MDD showed an improvement in depressive and anhedonic symptoms [36]. Most of our individuals' last reported mood was depression, the pathophysiological relevance of KCNQ3 in suicide could be the result of a similar abnormality from the resilience studies, where downregulation in the DLPFC of individuals who die by suicide, may derive in an unstable neuronal resting potential that may have an impact on resilience, depression, and suicide.…”
Section: Discussionmentioning
confidence: 99%
“…There were found 413 articles; 204 articles in Pubmed, 117 articles in Web of Science and 92 articles in SCOPUS. The final selection was 65 articles included, subdivided in: 11 articles that studied functional connectivity only at baseline, three related of the therapeutic response to psychopharmacotherapy (Goldstein-Piekarski et al, 2018;Vai et al, 2016), four to psychotherapy (Sambataro et al, 2018;Dunlop et al, 2017;Walsh et al, 2017) two related to TMS response (Du et al, 2018;Ge et al, 2017) and two related to tVNS response Wang et al, 2018b); and 54 articles that studied functional connectivity before and after antidepressant treatment: including 28 articles with psychopharmacotherapy (Yang et al, 2014;Wang et al, 2014;Li et al, 2016;Li et al, 2017;Karim et al, 2017;Tadayonnejad et al, 2016;Qin et al, 2015;Altinay et al, 2016;Evans et al, 2018;Tan et al, 2018;Admon et al, 2017;Yang et al, 2016;Abdallah et al, 2017;Abdallah et al, 2018), seven articles with psychotherapy Jacobs et al, 2016;Chattopadhyay et al, 2017;Young et al, 2018;Yokoyama et al, 2018), 11 with electroconvulsive therapy (ECT) (Wei et al, 2014;Wang et al, 2018;Perrin et al, 2012;Abbot et al, 2014;Mulders et al, 2016;, four with transcranial magnetic stimulation (rTMS) Kang et al, 2016;Taylor et al, 2018;Baeken et al, 2017) and two with vagus nerve stimulation (Fang et al, 2016;, and two with acu...…”
Section: Quality Analysismentioning
confidence: 99%